IMPLEMENTASI SISTEM INA-CBGs TERHADAP EFISIENSI PEMBIAYAAN DAN MUTU LAYANAN RUMAH SAKIT DI ERA JKN: SEBUAH TINJAUAN LITERATUR - Rosdian Tomalima; Ansarul Fahrudda (PT. Hasba Edukasi Mandiri, 2026)
Background: The implementation of the Indonesian Case-Based Groups (INA-CBGs) system involves a persistent tension between cost containment and quality of care that threatens the financial sustainability of both hospitals and the National Health Insurance (JKN) scheme. Objective: To synthesise current evidence on how INA-CBGs implementation affects hospital financing efficiency and quality of care in the JKN era. Methods: A systematic literature review was conducted following the PRISMA 2020 guideline. Google Scholar, PubMed, ScienceDirect, Scopus, and Garuda were searched for studies published between 2014 and 2026, using Boolean combinations of the terms INA-CBGs, cost analysis, pending claims, and clinical-pathway compliance. Methodological quality was appraised with the Joanna Briggs Institute (JBI) critical appraisal tools, and the twelve eligible studies were synthesised narratively using the synthesis-without-meta-analysis (SWiM) approach. Results: Three themes emerged. First, complex cases and class-3 inpatients showed a predominantly negative cost gap (an ischaemic-stroke deficit averaging IDR 214,049 per patient, equivalent to an extrapolated annual deficit of about IDR 1.26 billion). Second, pending-claim rates varied across hospitals (1.99%–4.4%) and were driven mainly by clinical (up to 60.9%) and coding (33.6%) factors. Third, clinical-pathway compliance was low (80% of hospitals below 50%), despite consistent evidence that greater adherence reduces cost, length of stay, and complications. Conclusion: INA-CBGs has not yet achieved an efficiency–quality balance. Strengthening clinical pathways through routine audit, joint training, evidence-based tariff adjustment, and claim digitalisation is needed to safeguard JKN sustainability (claim ratio ≈108%).